MENJAWAB MIMPI KESEJAHTERAAN NELAYAN TRADISIONAL DI KELURAHAN MALALAYANG I KOTA MANADO PROPINSI SULAWESI UTARA - Wagiu, Max (Sam Ratulangi University, 2011)
Economic and social prosperity is a dream of all traditional fishermen, particularly those who live in Malalayang I, Manado, North Celebes. This study used interviews to gather the information. Results found that 1) the local fishermen need to move to a semi-industrial fishing gear and boat in order to increase their catches; 2) the fishermen need to have an investment support to provide better fishing gears. Improvement in their economic and social conditions would bring improvements in social relationship among local fishermen.